THE DIFFERENCES BETWEEN MODAL VERBS IN ENGLISH AND GERMAN LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the differences between modal verbs in English and German, two widely spoken languages with unique grammatical systems. Although both languages use modal verbs to express similar meanings - like ability, permissio, and obligation - their structure and usage are quite different. This comparison helps learners avoid common mistakes and improve fluency in both languages. These insights are especially helpful for students learning English and German as a second language.